Pogostemon anamudicum (Lamiaceae): A new species from Sky Island of Kerala, India - Ravichandran, Kanagaraj; Jose, Robi Aloor; Melakath, Sumod; Sujanapal, Puthiyapurayil (Phytotaxa, 2025)
Pogostemon anamudicum, a new species from Anamudi hills, Idukki district, Kerala is described and illustrated. The species show similarities with Pogostemon raghavendranii, but is unique in the shape and size of stem, leaves, bracts, sepals, petals and ovary. A detailed description, accompanied by diagnostic characters that distinguish closely related species, along with color photographs is provided.